2021
DOI: 10.3390/medicina57040357
|View full text |Cite
|
Sign up to set email alerts
|

Mild Head Trauma: Is Antiplatelet Therapy a Risk Factor for Hemorrhagic Complications?

Abstract: Background and objectives: In patients who receive antiplatelet therapy (APT), the bleeding risk profile after mild head trauma (MHT) still needs clarification. Some studies have demonstrated an association with bleeding risk, whereas others have not. We studied the population of our level II emergency department (ED) trauma center to determine the risk of bleeding in patients receiving APT and whether bleeding results not from antiplatelet agents but rather from age. We assessed the bleeding risk, the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
1
17
0
1
Order By: Relevance
“…As reported in the pathophysiology of trauma, the barotrauma can affect several organs [60][61][62][63][64][65][66][67][68][69]. The most frequent injuries involve the sinuses and/or middle ear, but barotrauma may also cause facial, tooth, gastrointestinal (GI), pulmonary (pneumothorax, pulmonary hemorrhage), and mediastinal injuries.…”
Section: Physiopathologymentioning
confidence: 99%
“…As reported in the pathophysiology of trauma, the barotrauma can affect several organs [60][61][62][63][64][65][66][67][68][69]. The most frequent injuries involve the sinuses and/or middle ear, but barotrauma may also cause facial, tooth, gastrointestinal (GI), pulmonary (pneumothorax, pulmonary hemorrhage), and mediastinal injuries.…”
Section: Physiopathologymentioning
confidence: 99%
“…Indeed, studies have found that the risk of bleeding is significantly higher with anticoagulants as compared to antiplatelets alone (11). In the case of patients sustaining TBI, research suggests that preinjury use of anticoagulants (12) is a significant risk factor for developing ICH after TBI whereas corresponding evidence for antiplatelet drugs is ambiguous (13,14). Recent meta-analysis studies have assessed the impact of preinjury anticoagulation on outcomes of general trauma and TBI patients and have noted significantly increased mortality in anticoagulant users as compared to controls (1,10).…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulant therapies are suitable for multiple indications, and they were applied in several cohort studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The use of these drugs aggravates the risk of traumatic intracranial injury and influences the clinical outcomes after MHI and blunt head trauma [ 16 , 17 , 18 , 19 , 20 , 21 ]. However, there are no clear guidelines about the management of patients treated with vitamin K antagonist (VKA), new oral direct anticoagulants (DOACs), and antiplatelet agents (APT), unless they underwent a head CT scan upon admission to the ED, and after 24–48 h. As the use of DOACs is becoming more frequent, there has been a more tangible interest in this topic, as well as prospective studies and literature reviews [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
mentioning
confidence: 99%
“…We conducted a study to assess the bleeding risk profiles of patients admitted to the ED for MHI under DOACs and traditional VKAs [ 16 ]. The primary endpoint was to dictate the difference between the recurrency and complications of post-traumatic ICH following MHI.…”
mentioning
confidence: 99%